Penerapan Model Pembelajaran Kooperatif Teknik Snowball Throwing Dalam Meningkatkan Pemahaman Siswa Pada Materi Bahaya Hasad Di Kelas X MA Yasti Pada Mata Pelajaran Akidah Akhlak - Nurdzakia, Syalwa; Rosadi, Adi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE APPLICATION OF THE SNOWBALL THROWING TECHNIQUE COOPERATIVE LEARNING MODEL IN IMPROVING STUDENTS' UNDERSTANDING OF THE DANGERS OF EVIL IN CLASS X OF MADRASAH ALIYAH YASTI IN THE SUBJECT OF MORAL FAITH Character education in Islam plays an important role in shaping students' morals, including their understanding of the dangers of hasad (envy). However, at the Madrasah Aliyah (MA) level, students' understanding of the negative impacts of hasad remains low, partly due to less interactive teaching methods. This study aims to improve students' understanding of the dangers of hasad through the Snowball Throwing technique. This research employs Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observations, and documentation. The subjects of this study were 21 tenth-grade students at MA Yasti Cisaat. The results show that optimizing cooperative learning through the Snowball Throwing technique is effective in enhancing students' understanding of hasad, as well as increasing engagement and learning outcomes in the Aqidah Akhlak subject. This is evidenced by an increase in the average learning score from 77.62 to 93.81 and mastery learning from 76.19% to 100% in the second cycle. Additionally, student and teacher activity levels also improved significantly, proving that the Snowball Throwing model can create a more interactive and effective learning environment.